Interpreting soft sediment deformation and mass transport deposits as seismites in the Dead Sea depocenter - Lu, Yin; Waldmann, Nicolas; Alsop, G. I. (Journal of geophysical research. Solid earth, 2017)
We have studied the history of earthquakes over the past 70 kyr by analyzing disturbed sedimentary layers around the margins of the Dead Sea. However, we know little about disturbances in the basin depocenter, where water depth is 300 m, and accessible only by drilling. In this study, we compare disturbances from the Dead Sea depocenter, with the contemporaneous earthquake record ( 56-30 ka) that was recovered on the western margin of the lake. This comparison allows us to discern the characteristics of disturbance in the different subaqueous environments and identify the source and sedimentary process of mass transport deposits. Our observations indicate that (i) the long disturbance sequences in the Dead Sea depocenter are composed of in situ deformation, slump, and chaotic deposits; (ii) earthquake-triggered Kelvin-Helmholtz Instability is a plausible mechanism for the in situ deformation in the lake center; (iii) the slump is slope area sourced; (iv) the unit of chaotic deposits is lakeshore sourced; and (v) earthquake-triggered slope instability is a viable mechanism for the slump and chaotic deposits. We further suggest that long sequences of disturbance in seismically active lake depocenters can be used to infer earthquake clusters.
Gesehen am 16.10.2018